Potential of Green Gram Flour as an Enrobing Material for Papaya-Pulp Enriched Chicken Nuggets - Para, Parveez Ahmad; Kumar, Sunil; Raja, Waseem Hussain; Bhat, Z.F.; Kumar, Arvind (Journal of Meat Science, 2015)
A study was conducted to evaluate the possibility of utilization of green gram flour (GGF) as an enrobing material for papaya pulp-enriched chicken nuggets. GGF was used at two different levels in the batter mix viz. 25 % (w/w) and 35 % (w/w) separately and analyzed for various quality parameters. The products developed were assessed for various physicochemical, proximate and sensory parameters. A significant effect (p< 0.05) was observed on cooking yield, moisture percent, ether extract, ash content and crude fiber content of the products. Significantly (p<0.05) higher cooking yield, ether extract, ash and crude fiber content was observed for the products enrobed with 35 % GGF in comparison to nuggets enrobed with 25 % (w/w) GGF. Non-significant (p> 0.05) change was observed in colour and appearance, juiciness and flavour, however, a significant (p< 0.05) decrease was noted in the scores of texture and overall acceptability with increase in the level of green gram flour in the batter mix. Based on various quality parameters, 25 % level of GGF was optimized as best for enrobing of papaya pulp-enriched chicken nuggets.